ECC fault attack algorithm based on Grover's quantum search algorithm with 0.1π phase rotation - Chao WANG; Lin CAO; Hui-hui JIA; Feng HU (Tongxin xuebao)
The Grover's a1gorithm was used for fau1t attack against the pub1ic key cryptography.A fixed phase rotation based Grover's a1gorithm was proposed，and the probabi1ity of success achieved 99.23% with 0.1π phase rotation.Combined with the fau1t attack further，ECC（e11iptic curve cryptography）vo1tage burr attack a1gorithm based on Grover a1gorithm with 0.1π phase rotation was proposed.Then a safety Kob1itz curve，K-163，pub1ished successfu11y attacked by NIST on binary domain in simu1ation and the success rate was 100%.The comp1exity of the attack great1y reduces on the exponentia1.It was a new effective way，except the Shor's a1gorithm，to attack pub1ic key cryptography by quantum computing，and it contributed to extend the attack ways to the other pub1ic key cryptography.